PROFILE OF ADOLESCENT RESILIENCE IN SELF-HARM BEHAVIOR IN MAKASSAR CITY - Aryani, Farida; Pandang, Abdullah; Insani, Ainun (Lembaga Penelitian Mahasiswa Penalaran UNM, 2024)
The phenomenon of suicide in adolescents continues to increase every year. Self-harm behavior is one of the initial causes of suicidal ideation in adolescents. Adolescents' inability to cope with physical, psychological and environmental changes has a significant impact on various aspects of adolescents' lives. It is important for adolescents to have the ability to face problems, survive and recover after facing changes and challenges. However, adolescent resilience is also influenced by individual adolescents and their social environment. This study aims to analyze adolescents' resilience to self-harm behavior, This research was carried out in Makassar City for junior high school students using the Resilience Scale for Adolescents. The results of the study on 164 adolescents in Makassar City showed low categories in indicators of family environment, personal ability, social competition, and study/work patterns.